(untitled) (Acta Horti Botanici Bucurestiensis, 2025)
In the C. Studniczka’s herbarium we have found new herbarium folder which contain herbarium samples from families: Salicaceae, Pinaceae, Ephedraceae, Taxaceae and Cupressaceae. Most of the analysed herbal material (117 herbarium sheets, with 323 samples of herbal plants) in this part of the C. Studniczka’s herbarium were collected in Europe (105 herbarium sheets). According to the labels, the majority of herborized material was collected in the area of Austria (26 herbarium sheets). Most herbarium sheets belong to Flora von Wien collection (9). In reference to the part of Studniczka’s herbarium which has already been analysed, there is one botanist or collector which is mentioned for the first time: Brotherston. Also collections listed for the first time are: Ex. Herb. A. Brotherston, Kelso and Herbarium R. Fritβe in Rybnik. Most herbarium sheets were collected by Studniczka himself (36). The oldest herbarium sheets dates from 1856, where as the newest ones date from 1902. The exact year of collection is missing from 13 herbarium labels.